A CASE OF PSEUDOANEURYSM OF THE SUPERIOR GLUTEAL ARTERY AFTER TRANSILIAC-TRANSSACRAL SCREW FIXATION FOR FRAGILITY FRACTURE OF THE PELVIC RING - NISHIZAWA, Go; MATSUOKA, Tatsuki; HAO, Motoshi; INAGAKI, Naoya; SAITO, Mitsuru; SASAMOTO, Shohei; KOMUKAI, Nobuyuki (Journal of the Japanese Association for the Surgery of Trauma, 2023)
Transiliac-transsacral screw (TITS) fixation is a minimally invasive procedure for pelvic ring fractures in the elderly. However, the diagnosis, treatment, and prevention of vascular injury as a complication remains limited. Herein, we present a 70-year-old man who underwent percutaneous TITS fixation for a Rommens type IIc fragility fracture of the pelvic ring. After surgery, a pseudoaneurysm was found in the deep branch of the superior gluteal artery (DSGA) adjacent to the TITS insertion site at S2. Coil embolization was performed. After embolization, there was no further deterioration in anemia, and bone union was observed. The distance between the TITS insertion point and the DSGA was small ; thus, there was an increased risk of arterial injury. When inserting TITS, it is important to confirm the course of the superior gluteal artery branch by contrast-enhanced CT before surgery and to ensure the safe performance of surgery with adequate protection of the surrounding tissue.